Analyzing the Effect of Instagram on Entrepreneurial Intention (Case of Study: Semnan University Students) - Meisam Modarresi; Shaghayegh jalilvand (مطالعات رسانه‌های نوین, 2023)
IntroductionEntrepreneurship has drawn much attention in recent times due to its ability to create job opportunities, thereby addressing the issue of employment and unemployment. Resolving unemployment is one of the most pressing social challenges that policymakers are facing. Entrepreneurship is a solution to this problem, and students possessing entrepreneurial skills and motivation can lead to resolving these issues. In this regard, the aim of the present study is to investigate the effect of Instagram on entrepreneurial intention among Semnan University students.Methodology:The research follows a quantitative approach, with a functional purpose. The method of data collection is descriptive survey, while the time frame is single-section. The statistical population of this study is composed of 2,000 students who study at the Faculty of Economics, Management and Administrative Sciences, as well as the Faculty of New Sciences and Technologies at Semnan University, and are members of Instagram. Specifically, the population consists of students who follow entrepreneurial pages on Instagram.A non-probability sampling method, namely stratification, was employed, and a simple random sampling method was used to select a sample of 322 individuals. The data collection tool used in this study is a standard questionnaire that was adapted to the research objectives.FindingsRegarding the effect of Instagram on entrepreneurial intention, the research results revealed a significant impact. The community of entrepreneurs on Instagram have provided students with the confidence to transform their business ideas into reality. In addition, this social network has had the greatest impact on social norms and entrepreneurial attitudes; that is, students communicate with their family, friends and professors on the Instagram social network, and this communication has affected the social and mental norms of students. In addition, this social network has made entrepreneurship students think about independent business.ConclusionInstagram has been found to play a significant role in fostering entrepreneurial intention. The social network has strengthened students' confidence to start a business idea. By extension, these findings emphasize the importance of educating students about entrepreneurship and its benefits, including their ability to create employment opportunities. However, it's important to note that future research may reveal additional factors that impact the relationship between Instagram